2013
DOI: 10.5480/1536-5026-34.2.95
|View full text |Cite
|
Sign up to set email alerts
|

An Intervention to Promote Civility Among Nursing Students

Abstract: Expansion of this study to further test the impact of civility-focused journal clubs is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(51 citation statements)
references
References 11 publications
1
48
2
Order By: Relevance
“…Journal clubs have been used to teach students civility, helpfulness to peers, coping strategies, collaboration, and problem solving. 14,15 Undergraduate nursing student journal clubs also have been used successfully to foster professional development. 16 Not only are journal clubs useful in the academic setting, but they also have value in the clinical environment.…”
Section: Journal Clubsmentioning
confidence: 98%
“…Journal clubs have been used to teach students civility, helpfulness to peers, coping strategies, collaboration, and problem solving. 14,15 Undergraduate nursing student journal clubs also have been used successfully to foster professional development. 16 Not only are journal clubs useful in the academic setting, but they also have value in the clinical environment.…”
Section: Journal Clubsmentioning
confidence: 98%
“…In a pilot study, Jenkins and colleagues reported students identified overtly rude behaviors among their peers, such as eye-rolling, snickering, and talking while others were speaking [3] . Students have also described an atmosphere of academic competition in which peers refused to help others study and intentionally provided them with erroneous information [14] .…”
Section: Incivility and Nursing Educationmentioning
confidence: 99%
“…Incivility is a significant problem in clinical settings as well; students have reported being ignored and treated unfairly by hospital nurses [15] . Nurse educators have developed interventions to reduce incivility among nursing students, including posting codes of conduct, clarifying behavioral expectations in classroom and clinical settings, and role modeling [3,4,12] . However, only two studies were found describing journal clubs as a means to encourage civility [3,4] .…”
Section: Incivility and Nursing Educationmentioning
confidence: 99%
See 2 more Smart Citations